Implementasi Sanksi Pidana Terhadap Anak Pelaku Tindak Pidana Narkotika Dalam Sistem Peradilan Pidana Anak - Pasaribu, Abas Mei Julita; Sirait, Timbo Mangaranap (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Children are considered valuable assets of the nation that must be protected, but their involvement in narcotics crimes is increasing, therefore it is necessary to continually study the implementation of criminal sanctions against children who commit narcotics crimes in the juvenile criminal justice system in Indonesia through case study number 6/Pid.Sus -Children/2021/Pn. Amb.. This research uses normative juridical methods to examine the application of legal rules to children involved in narcotics crimes. The results of the research show that the process of investigating and applying articles to child drug offenders needs to pay attention to the principles of restorative justice, which emphasizes rehabilitation and guidance rather than punishment alone. In addition, the implementation of the Juvenile Criminal Justice System Law aims to provide special protection for children in conflict with the law, ensure their rights are fulfilled, and minimize the negative impact of the judicial process. This research emphasizes the importance of a children's rights and restorative justice-based approach in handling narcotics cases involving children, so that they can become productive individuals in the future.